Decarbonising our food systems: contextualising digitalisation for net zero - Pearson, Simon; Brewer, Steve; Manning, Louise; Bidaut, Luc; Onoufriou, George; Durrant, Aiden; Leontidis, Georgios; Jabbour, Charbel; Zisman, Andrea; Parr, Gerard; Frey, Jeremy; Maull, Roger (Frontiers in Sustainable Food Systems, 2023)
ABSTRACT The food system is undergoing a digital transformation that connects local and global supply chains to address economic, environmental and societal drivers. Digitalisation enables firms to meet sustainable development goals (SDGs), address climate change and the wider negative externalities of food production such as biodiversity loss, and diffuse pollution. Digitalising at the business and supply chain level through public-private mechanisms for data exchange affords the opportunity for greater collaboration, visualising and measuring activities and their socio-environmental impact, demonstrating compliance with regulatory and market requirements and providing opportunity to capture current practice and future opportunities for process and product improvement. Herein we consider digitalisation as a tool to drive innovation and transition to a decarbonised food system. We consider that deep decarbonisation of the food system can only occur when trusted emissions data are exchanged across supply chains. This requires fusion of standardised emissions measurements within a supply chain data sharing framework. This framework, likely operating as a corporate entity, would provide the foci for measurement standards, data exchange, trusted and certified data and as a multi-stakeholder body, including regulators, that would build trust and collaboration across supply chains. This approach provides a methodology for accurate and trusted emissions data to inform consumer choice and industrial response of individual firms within a supply chain.